Study of Sun Protection Factor (SPF) Batik Textile Fabric on Solar Radiation in Pekalongan - Yeni Rima Liana; Fianti Fianti; Upik Nurbaiti (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
The amount of sunscreen ability is determined through the value of a person's Sun Protection Factor (SPF) when under the sun without experiencing sunburn. This study aims to measure the intensity of sunlight received by batik textile fabrics and SPF measurements to determine the ability of these fabrics to protect sunlight radiation. The research was conducted at the Sorogenen area in Pekalongan, Central Java. The intensity data collection is done during the sunny weather with 300C - 320C temperature. The SPF value is calculated by comparing the intensity of sunlight without and with a protective batik cloth. Between 10:00 a.m. and 2:00 p.m. (GMT +7), the average intensity is 85.160 lux to 113.400 lux. The results obtained by fabric with a thickness of 2 mm have an SPF greater than fabric with a thickness of 1 mm. Cotton fabric has the ability to protect against sunlight better than satin and Mori fabric. A blue cotton cloth owns the most significant SPF value with a thickness of 2 mm of 36.06. In comparison, the smallest SPF value is owned by yellow Mori fabric with a thickness of 1 mm of 5.24.